(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The demand for coffee in the Philippines has increased in recent years, making it an ideal location for opening a coffee shop. With the establishment of the EMA Town Centre, businesses in the area can access a larger customer base from other barangays. This study aims to analyse how marketing tools affect the business performance of Qhaveh Khaneh, an emerging coffee shop concept in the area. Qhaveh Khaneh needs suitable strategies for different demographic profiles, including age groups, gender and occupation. They should also enhance and maximise their selling methods to make their brand more appealing to the market. Acquiring and sustaining trends is important for the welfare of employees and customers. The most significant concerns are the lack of sales, stiff competition and weak marketing presence, and an advanced action plan is needed to improve operations. The study found that respondents were mostly between 21-25 years old, pricing was fair, food was flavourful, and staff was friendly. Marketing tools such as direct marketing and word-of-mouth also had a positive impact. Qhaveh Khaneh’s bond with brand identity and food and beverage safety standards were also well-implemented. However, lack of sales, stiff competition and weak promotional presence were identified as areas for improvement.